Comparative assessment of road traffic noise through 2D noise mapping: A case study of an urban area - Alam, Pervez; Mazhar, Mohd. Aamir; Ahmad, Kafeel; Aslam, Zishan; Afsar, S. S.; Husain, Atif (Frontiers in Sustainability, 2022)
Noise pollution has risen to a worrying degree in all zones of the city (residential, commercial, industrial, and silent) because of the rapid rise in urbanization, industrialization, and other connectivity of transport systems in all zones of the city. It has always been challenging to identify noise hotspots where immediate remedial measures are required. In addition to providing the propagation of noise in the X and Z direction, 2D noise mapping is an essential method for identifying regions where noise levels may reach a hazardous level. Thus, the comparative examination of all residential areas inside a city provides a clear picture of noise exposure. The main focus of this study is to carry out comparative analysis of noise exposure level of selected locations such as residential commercial, industrial and silent area of Delhi city using 2D noise maps. For noise monitoring, Sound Level Meter (SLM) Larson & Davis 831 in compliance with the standard procedure of CPCB is used for monitoring peak traffic hours of working day and night. After that, using sound PLAN (acoustic) and MapInfo Pro, 2-D (Desktop GIS) noise maps were developed, visualized, and analyzed. According to the findings, residential areas have been recorded as having the highest levels of noise, followed by commercial and silent zones, and industrial areas have been seen to have the lowest levels of noise. The high noise level in residential area may be due to heavy traffic volume and road surrounded by high rise buildings. Whereas minimum noise has been observed in industrial area because the industries along the major roads have been surrounded with parapets and trees. As a result, only a small amount of industrial noise entered major highways/roads. Additionally, 2D noise map revealed that the surrounding structures of road (high rise buildings, brick walls, grilled boundaries, trees etc.) significantly influence propagation of noise in all directions. These maps may also be utilized by decision makers in the process of formulating noise control strategies or implementing corrective measures.